PENGELOMPOKAN KABUPATEN/KOTA DI PROVINSI JAWA TENGAH BERDASARKAN ANGKA PARTISIPASI PENDIDIKAN JENJANG SMA/MA/PAKET C DENGAN FUZZY SUBTRACTIVE CLUSTERING - Onny Kartika Hitasari; Diah Safitri; Suparti Suparti (Jurnal Gaussian, 2015)
Education is one aspect of nation building is very important to realize the human resource development and national character. Awareness of the importance of education can be seen through education enrollment rates. This study aims to classify the enrollment rates in the district / city Central Java. The data used is the Gross Enrollment Rate (GER), Net Enrollment Rate (NER) and School Enrollment Rate (SER) at the district / city in Central Java Province in 2013. The grouping method used in this study is Fuzzy Subtractive Clustering. The results showed that the best cluster grouping enrollment rates in Central Java Province which consists of 4 clusters with value of cluster variant is 0.00749 and radii between 0.35 to 0.50. Keywords: education participation rate, GER, NER, SER, Fuzzy Subtractive Clustering